Role of bile acids in atherogenesis: review - A. S. Safaryan (Кардиоваскулярная терапия и профилактика, 2024)
The review describes the metabolism of bile acids (BAs) in the human body, their effect on cholesterol metabolism and the development of atherosclerosis, which remains one of the most pressing problems in medicine. The problem of cholestasis is discussed, which is often found in patients with cardiovascular diseases with comorbidities, including non-alcoholic fatty liver disease and which plays a key role in the development of many complications associated with impaired BA metabolism, including hyperlipidemia, metabolic syndrome. Cholestasis treatment, which allows restoring normal cholesterol levels, are considered. Timely administration of ursodeoxycholic acid makes it possible to prevent atherosclerosis (primary prevention of atherosclerosis), because with normal bile metabolism, the levels of proatherogenic lipids are normalized and the production of inflammatory mediators, high levels of which contribute to atherogenesis, decreases. In this review, the author presents the important role of bile metabolism in the primary and secondary prevention of atherosclerosis and the possibility of solving this issue by prescribing ursodeoxycholic acid and changing lifestyle.